Comparison of the performance of three different ecophysiological life forms in a sandy coastal restinga ecosystem of SE-Brazil: a nodulated N₂-fixing C₃-shrub (Andira legalis (Vell.) Toledo), a CAM-shrub (Clusia hilariana Schltdl.) and a tap root C₃-hemicryptophyte (Allagoptera arenaria (Gomes) O. Ktze.) - Gessler, Arthur; Nitschke, Renate; de Mattos, Eduardo A; Zaluar, Henrique L. T; Scarano, Fabio R; Rennenberg, Heinz; Lüttge, Ulrich (Trees (Berlin, West), 2008)
In a sandy coastal restinga ecosystem NE of Rio de Janeiro, Brazil, subject to environmental stress due to high irradiance, high temperature and low water supply, a comparative ecophysiological study of three species of different morphotypes and physiotypes was conducted during the dry season. The morphotypes were two shrubs, Clusia hilariana Schltdl. and Andira legalis (Vell.) Toledo, and the taproot hemicryptophyte Allagoptera arenaria (Gomes) O. Ktze. The physiotype differences were that C. hilariana was performing crassulacean acid metabolism (CAM), A. legalis was a nodulated N₂ fixing legume and A. arenaria had ample access to water by ground water tapping roots. All three species were light stressed and showed photoinhibition and high maximum values of non-photochemical quenching of chlorophyll fluorescence. δ¹³C values of bulk leaf organic matter (which integrate over the life span of the leaf) and instantaneous gas exchange patterns demonstrated that C. hilariana was performing CAM and the other two species C₃-photosynthesis. A. arenaria performed generous and A. legalis conserving use of water. Based on the CO₂ concentrating mechanism of CAM C. hilariana had the highest maximum rates of apparent photosynthetic electron transport, ETRmax. Uptake of atmospheric CO₂ in the afternoon (phase IV of CAM) was expressed weakly showing that the plants were under some but not severe water stress. A. legalis showed the highest levels of total N and soluble non-protein N-compounds in its organs due to N₂ fixation which, however, did not confer a higher photosynthetic capacity that must have been limited by factors other than nitrogen supply. Accumulation of amino compounds like proline and γ-aminobutyric acid in leaves of A. legalis which are known to act as osmoprotectants is likely to indicate drought stress in the dry season. Maximum net CO₂ uptake of photosynthesis was higher in the water spending A. arenaria than in A. legalis. The comparative analysis of physiological traits characterised either instantaneously or integrated over the longer term shows that in addition to morphotypic characteristics physiotypic characteristics are important for space occupation and niche acquisition of the plants in the restinga.